Increasing Local Original Revenue (PAD) for Tourism Villages with a Trustworthy Perspective to Avoid Fraud - Sari, Fangela Myas; Safitri, Anni (Jurnal Iqtisaduna, 2025)
This study aims to provide training on increasing local revenue (PAD) with a trustworthy perspective to avoid fraud. Limitations in the use of digital tourist destination sites encouraged the research team to take part in efforts to support the growth and development of local revenue (PAD) in Pekalongan Regency. The results of this Community research activity, namely the management of tourist villages who initially did not utilize digital sites to promote their tourism, are now able and ready to create digital sites and seen from a trustworthy perspective, are very useful because they make humans have a trust that must be fair and transparent in its management to avoid fraud